Connecting to the trail: Natural spaces as places of healing. (17th November 2022) - Harmon, Justin; Kyle, Gerard
Abstract: The concept of "place" has been explored for decades, examining how specific geographic locales impact social meanings and interactions, sentimentality associated with a specific environment, and the construction of identity through prolonged place interaction. While meanings often differ based on individual history and interactions, physical environments are often symbolic; they may come to embody elements of potential, catharsis, restoration, or opportunity. In the context of nature, the diversity of meaning is often evidenced by an individual or groups' reverence for the natural place to their perceived quality of life. This study sought to explore how those diagnosed with cancer use natural spaces as a supportive resource in their healing process. As will be demonstrated, the profound benefit of repeated exposure to restorative natural environments for those diagnosed with cancer establishes how natural spaces become places of healing for people with serious illnesses.